Cyclooxygenase‐2 in cancer: A review - Hashemi Goradel, Nasser; Najafi, Masoud; Salehi, Eniseh; Farhood, Bagher; Mortezaee, Keywan (Journal of cellular physiology, 2019)
Cyclooxygenase‐2 (COX‐2) is frequently expressed in many types of cancers exerting a pleiotropic and multifaceted role in genesis or promotion of carcinogenesis and cancer cell resistance to chemo‐ and radiotherapy. COX‐2 is released by cancer‐associated fibroblasts (CAFs), macrophage type 2 (M2) cells, and cancer cells to the tumor microenvironment (TME). COX‐2 induces cancer stem cell (CSC)‐like activity, and promotes apoptotic resistance, proliferation, angiogenesis, inflammation, invasion, and metastasis of cancer cells. COX‐2 mediated hypoxia within the TME along with its positive interactions with YAP1 and antiapoptotic mediators are all in favor of cancer cell resistance to chemotherapeutic drugs. COX‐2 exerts most of the functions through its metabolite prostaglandin E2. In some and limited situations, COX‐2 may act as an antitumor enzyme. Multiple signals are contributed to the functions of COX‐2 on cancer cells or its regulation. Members of mitogen‐activated protein kinase (MAPK) family, epidermal growth factor receptor (EGFR), and nuclear factor‐κβ are main upstream modulators for COX‐2 in cancer cells. COX‐2 also has interactions with a number of hormones within the body. Inhibition of COX‐2 provides a high possibility to exert therapeutic outcomes in cancer. Administration of COX‐2 inhibitors in a preoperative setting could reduce the risk of metastasis in cancer patients. COX‐2 inhibition also sensitizes cancer cells to treatments like radio‐ and chemotherapy. Chemotherapeutic agents adversely induce COX‐2 activity. Therefore, choosing an appropriate chemotherapy drugs along with adjustment of the type and does for COX‐2 inhibitors based on the type of cancer would be an effective adjuvant strategy for targeting cancer. Cyclooxygenase‐2 (COX‐2) is frequently expressed in many types of cancers exerting a pleiotropic and multifaceted role in genesis or promotion of carcinogenesis and cancer cell resistance to chemo‐ and radiotherapy. COX‐2 is released by cancer‐associated fibroblasts (CAFs), macrophage type 2 (M2) cells, and cancer cells to the tumor microenvironment (TME). COX‐2 induces cancer stem cell (CSC)‐like activity and promotes apoptotic resistance, proliferation, angiogenesis, inflammation, invasion, and metastasis of cancer cells.